Aplikasi Pencatatan Pelanggaran Siswa melalui Whatsapp Gateway berbasis Web - Afifah Nur Utami; Murti Retnowo (Universitas Hamzanwadi, 2023)
In MTs Negeri 5 Klaten, recording violations committed by students is still recorded manually in a book, and reporting violations to parents is still printed on paper. For this reason, a system is needed that can assist in recording and reporting violations by building the system into a web. This study aims to build an application for recording student violations through a web-based WhatsApp gateway. The method used in this study uses prototyping. The data collection phase starts with problem identification by collecting data through observation and interviews. The prototyping phase is a temporary design of the software using context diagrams, data flow diagrams, and entity-rational diagrams. The stage of coding the system using the PHP programming language with the bootstrap framework and MySQL database. The data analysis techniques used are qualitative. Qualitative analysis in the form of data collection is conducted through observation and interviews Application testing is carried out by Blackbox testing, which aims to determine whether the functions, inputs, and outputs of the system are built by the required system specifications. The findings are in the form of a student violation recording application through the web-based WhatsApp gateway, which shows that the application is running well, is feasible to use, and can help schools convey student violation report information to parents quickly and accurately.